Long‐term follow up of 3 T MRI‐detected brain lesions after percutaneous catheter‐based left atrial appendage closure. Issue 2 (8th May 2018) - Bellmann, Barbara; Rillig, Andreas; Skurk, Carsten; Leistner, David Manuel; Haeusler, Karl Georg; Lin, Tina; Geran, Rohat; Koehler, Luzie; Guttmann, Selma; Tscholl, Verena; Roser, Mattias; Lenz, Klaus; et al.
Abstract: Background: Left atrial appendage closure (LAAC) for stroke prevention is an increasingly performed intervention. Aims: This prospective study aims to evaluate the incidence of long‐term magnetic resonance imaging (MRI)‐detected brain lesions as well as potential changes of neurocognitive function after percutaneous LAAC. Methods: Brain MRI at 3 T was performed within 24 hr before and after LAAC. A follow‐up MRI was carried out after three months. Neuro‐cognitive examination using the National Institutes of Health Stroke Scale (NIHSS) score and the Montreal Cognitive Assessment (MoCA) Test was performed. Results: Successful device implantation was achieved in all 25 patients (age 74.6 ± 10.2 years, male = 17) using the Amulet ( n  = 20), Occlutech ( n  = 3), or a Lambre ( n  = 2) device. In 12/25 (48%) patients, acute brain lesions (ABL) were detected after LAAC. A three‐month follow‐up MRI was performed in seven patients, and no new ABLs were seen. In 5/7 (71%) patients, there were no residual changes from the ABLs detectable. However, the FLAIR sequence was still positive in two patients. After LAAC, there were no significant differences in the MoCA‐test (mean 24.3 ± 4.5 vs. 23.5 ± 4.5; P  = 0.1) and the NIHSS‐score (mean 0.9 ± 1.6 vs. 1.2 ± 1.8; P  = 0.1). This was the same at the three‐month follow‐up (MoCA‐test 23.5 ± 4.5 vs. 23.8 ± 2.7; P  = 0.3; NIHSS‐score 1.2 ± 1.8 vs. 1.0 ± 0.8; P  = 0.4). Conclusion: While new MRI‐detected brain lesions are commonly observed after percutaneous LAAC, ABLs were no longer detectable in 71% of the patients at the three‐month follow‐up. There were no significant changes in neurocognitive function after LAAC and at the three‐month follow‐up.